Mortality pattern of cardiovascular diseases in the medical wards of a tertiary health centre in a rural area of Ekiti State, Southwest Nigeria. - Ogunmola, Olarinde J; Akintomide, Antony O (Asian Journal of Medical Sciences, 2013)
Objective: To determine the basic demographic patterns of cardiovascular diseases, deaths, and the frequency of clinical causes of deaths in medical wards of a tertiary health centre in a rural area, south west Nigeria. Materials and methods: Retrospective analysis of patients’ records admitted into the medical wards of Federal Medical Centre IdoEkiti, Ekiti State, South west Nigeria were conducted. The study subjects were patients of 16 years and above who died of cardiovascular diseases from January 2009 to December 2012. Data analysis was done using SPSS Version 16. Results: A total of 681 patients with cardiovascular diseases were admitted in medical wards within the study period, of which 70 died with crude mortality rate of 10.3%. Male mortality were 30 (42.9%) and females 40 (57.1%) ratio 1:1.3. The age range was 25 – 100 years with mean of 66.4 + 16.3 years, with more deaths occurring in the elderly (72%). The most frequent cause of deaths was stroke (68.6%). Conclusion: Females contributed the highest number of cardiovascular disease admission and crude mortality. Stroke was responsible for over half of cardiovascular deaths, and hypertension was the commonest aetiological factors of cardiovascular disease deaths. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8030 Asian Journal of Medical Sciences 4(2013) 52-57